Plan de mejoramiento para la finca agropecuaria nuevo horizonte, ubicada en el barrio la Capilla, parroquia el Tambo, cantón Catamayo provincia de Loja - Alvarado Jaramillo, Carmen Yessenia (2016)
This research project entitled "Improvement Plan for Agricultural Farm New Horizont, Located in Barrio La Capilla, Parroquia El Tambo, Canton Catamayo Loja Province" had as its main objetives to make the diagnosis of the current situation of the agricultural farm "New Horizon" and the design of a proposed improvement plan for the farm, so we can define a series of short-, medium- and long-term, enable them to be an agricultural enterprise with sustainability over time. Within the methodology used to achieve the objectives, the following took place: Geographical farm location, weather conditions, within the research methods the analytical method used, the descriptive and deductive, variables used were analyzing internal and external environment, projecting the mission, vision, objectives and policies, strategies and selection of projects and overall programming and operational techniques are used as direct observation and interview the owner of the property, to obtain accurate and reliable information. The results show that the Agricultural Farm "New Horizont" is a unit with borrowing capacity building facility for both agricultural and livestock, which currently has no debt. Found opportunities outweigh the threats so took advantage of these opportunities to address the internal weaknesses and external threats. This proposal shows the different actions both in territorial, administrative and financial running and which are those that allow us to optimize existing production resources in the middle. Shares are reflected in the various programs to be executed, according to the schedule defined in the proposed Plan. Where it raises inter alia the hiring of personnel, implementation of the administrative department and within the estate winery, building adequate infrastructure for bovine animals and children, division of plots for short-cycle crops, implementation of an area of organic fertilizers. Implementation of an area of vegetables and redistribution of the area of fruit. As conclusions indicated that agricultural farm "New Horizon" is organized under a decaying administrative system without proper agricultural planning, which has an ideal crop diversification climatic variety, besides the mission, vision,objectives and policies are not defined so it is not clear the future of the company, so recruitment is recommended to monitor the activities developed on the farm, adopt the plan of appropriate selection of crops to maintain high productivity and soil fertility and the use of the mission, vision and policy objectives presented in this thesis project in order to strengthen the productive capacity of the farm, looking to get a return on their investment.